Penerapan Model Pembelajaran Kooperatif Tipe GQGA Untuk Meningkatkan Minat dan Hasil Belajar IPAS pada Murid Kelas V SD Inpres Mattontongdare Kecamatan Bajeng Barat Kabupaten Gowa - Mukminah, Mukminah; Yunus, Muh; Iskandar, Arifuddin (CV. Rayyan Dwi Bharata, 2025)
This research is a classroom action research that aims to increase interest and learning outcomes of social studies through the application of a GQGA-type cooperative learning model in grade V students of SD Inpres Mattontongdare, West Bajeng District, Gowa Regency. The subject of this study is a grade V student of SD Inpres Mattontongdare in West Bajeng District, Gowa Regency with a total of 28 students, consisting of 14 male students and 14 female students. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of the GQGA-type cooperative learning model has succeeded in significantly increasing students' interest in learning. In the first cycle, students' interest in learning was recorded to only reach 67%, but after the application of this model in the second cycle, students' interest in learning increased rapidly to 88%. This shows that the GQGA-type cooperative learning model is effective in arousing students' enthusiasm and involvement in the learning process, thereby increasing their motivation to learn better. The GQGA-type cooperative learning model has also proven to be very effective in improving student learning outcomes in science and science subjects. In the first cycle, only 61% of students achieved completeness, while 39% did not achieve completeness. However, in the second cycle, the number of students who did not complete dropped dramatically to only 7%, and the number of students who completed increased to 93%. This shows that the application of the GQGA-type cooperative learning model can help students understand the material better and achieve optimal results in social science learning.